Towards a viewpoint oriented design methodology for Multi-processor Real-Time Systems - Zhang, L.; Katwijk, J. van (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1994)
In this paper we describe a design methodology for the development of (potentially multi-processor) real-time system. Our proposed methodology differs fundamentally from current methodology and serves to help manage the complexity of massive-intensive systems. One of the distinguishing aspects of this methodology is in its ability to express timing constraints and verify to what extent such constraints are met. A second distinguishing aspect of this methodology is to develop a system according to five views of systems. In particular, the problems concerned with the transformation of the specifications into the parallel programs are addressed. The proposed methodology is applied to develop an onboard generator for generating transfer frames, complyannt to the CCSDS Recommendations [34], [35]. This onboard generator is implemented on a transputer network [1], [2].